A review of agent‐based modeling of climate‐energy policy. (1st April 2020) - Castro, Juana; Drews, Stefan; Exadaktylos, Filippos; Foramitti, Joël; Klein, Franziska; Konc, Théo; Savin, Ivan; van den Bergh, Jeroen
Abstract: Agent‐based models (ABMs) have recently seen much application to the field of climate mitigation policies. They offer a more realistic description of micro behavior than traditional climate policy models by allowing for agent heterogeneity, bounded rationality and nonmarket interactions over social networks. This enables the analysis of a broader spectrum of policies. Here, we review 61 ABM studies addressing climate‐energy policy aimed at emissions reduction, product and technology diffusion, and energy conservation. This covers a broad set of instruments of climate policy, ranging from carbon taxation, and emissions trading through adoption subsidies to information provision tools such as smart meters and eco‐labels. Our treatment pays specific attention to behavioral assumptions and the structure of social networks. We offer suggestions for future research with ABMs to answer neglected policy questions. This article is categorized under: Climate Economics > Economics of Mitigation Abstract : Thematic foci of the review.